1998
DOI: 10.1046/j.1537-2995.1998.38198141494.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential induction of P‐selectin expression on platelets by two cell separators during plateletpheresis and the effect of gender on the release of soluble P‐selectin

Abstract: This trial shows 1) that initial activation of platelets obtained with the MCS 3P is less than that of platelets obtained with the CS 3000 Plus; 2) that the increase in cP-selectin is a more sensitive marker for initial platelet activation than the expression of P-selectin on the surface; and 3) that the relative amount of cP-selectin is higher in women than in men given the same stimulus. Differences in platelet activation by various cell separators and the sex of the donor may contribute to variability of PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 16 publications
2
51
0
Order By: Relevance
“…This resulted in an increased formation of platelet-leucocyte aggregation through the PSGL-1 receptor and subsequent clearance from the circulation [19][20][21]. Some investigators have suggested that soluble sCD62p is a more sensitive marker for platelet activation than CD62p surface expression [22]. We could not detect any difference in sCD62p levels due to PRT, but we found increased baseline levels and decreased activation capacity that was more prominent after PRT treatment.…”
Section: Discussionmentioning
confidence: 60%
“…This resulted in an increased formation of platelet-leucocyte aggregation through the PSGL-1 receptor and subsequent clearance from the circulation [19][20][21]. Some investigators have suggested that soluble sCD62p is a more sensitive marker for platelet activation than CD62p surface expression [22]. We could not detect any difference in sCD62p levels due to PRT, but we found increased baseline levels and decreased activation capacity that was more prominent after PRT treatment.…”
Section: Discussionmentioning
confidence: 60%
“…Increased MPV has been described (30), although not all studies confirm this (31). Raised MPV is also a risk factor for MI (32) and, in addition, is a marker of platelet activation (33)(34)(35). However, the link between other aspects of platelet physiology in hypertension and the presence of TOD has not been previously documented (i.e., raised MPV and MPM and lower MPG).…”
Section: Discussionmentioning
confidence: 99%
“…This process has also been observed in other studies. During cardiopulmonary bypass, hemodialysis, plasmapheresis and plateletpheresis, progressive platelet activation can be detected [21, 27, 28, 29, 30]. Several factors may explain this process.…”
Section: Discussionmentioning
confidence: 99%